Logical Semantics in the “Stories for Rainy Days” by Naela Ali - Rada Mayasari; Masdiana Lubis; Dian Marisha Putri (Talenta Publisher, 2021)
This research aims to analyze the elaboration, extension, and improvement contained in the data. The data source of this research is Naela Ali’s story of rainy days written by Naela Ali as the best-selling short story in 2018. The research data is in the form of clauses collected from short stories on rainy days. The theory used to analyze the meaning of the data is a logical-semantic theory. From this study, There are 3 types of logical semantic found in “Stories for Rainy Days” Short Story By Naela Ali: elaboration, extension, and enhancement. this research concludes that there is 83 logical semantics (expansion) found in the